Kora bronzkori település(részlet) Kiskundorozsma határában - Major Réka (SZTE BTK Régészeti Tanszék Szeged, 2023)
In this study, I analysed the material of the Early Bronze Age features excavated in the area of Szeged, Kiskundorozsma–Sandpit No. 4, which can be classified as a settlement of the Makó–Kosihy–Čaka culture. Several features were excavated at this site, which were suggested to date to the Early Bronze Age, however, in most of them there were only few small, damaged pottery fragments not suitable for a more precise identification. The datable finds fit well into the material culture of the Makó culture, best exemplified by the fragments of the interior decorated bowls, but there are also elements that show the influence of other cultures. As is typical of the settlements of the Makó culture, household pottery was also more common here, but the number of fragments belonging to jugs and mugs is also significant. The jugs and some types of mugs are not among the basic vessel shapes of the Makó culture, but show a close resemblance to the drinking vessels of the Somogyvár–Vinkovci culture. A fragment of a cylindrical flask has also been found, which is one of the hallmarks of the Somogyvár– Vinkovci culture, its appearance also shows the links between the two cultures. The Early Bronze Age settlement has also yielded a chipped stone arrowhead, which appears in the Carpathian Basin with the Bell Beaker culture. Results of the archaeozoological examination are presented in the chapter on settlement structure. At the end of the paper, I will focus on the cultural connections of the Makó culture, based on the site discussed.